Canopy structure and topography jointly constrain the microclimate of human‐modified tropical landscapes. (23rd September 2018) - Jucker, Tommaso; Hardwick, Stephen R.; Both, Sabine; Elias, Dafydd M.O.; Ewers, Robert M.; Milodowski, David T.; Swinfield, Tom; Coomes, David A.
Abstract: Local‐scale microclimatic conditions in forest understoreys play a key role in shaping the composition, diversity and function of these ecosystems. Consequently, understanding what drives variation in forest microclimate is critical to forecasting ecosystem responses to global change, particularly in the tropics where many species already operate close to their thermal limits and rapid land‐use transformation is profoundly altering local environments. Yet our ability to characterize forest microclimate at ecologically meaningful scales remains limited, as understorey conditions cannot be directly measured from outside the canopy. To address this challenge, we established a network of microclimate sensors across a land‐use intensity gradient spanning from old‐growth forests to oil‐palm plantations in Borneo. We then combined these observations with high‐resolution airborne laser scanning data to characterize how topography and canopy structure shape variation in microclimate both locally and across the landscape. In the processes, we generated high‐resolution microclimate surfaces spanning over 350 km 2, which we used to explore the potential impacts of habitat degradation on forest regeneration under both current and future climate scenarios. We found that topography and vegetation structure were strong predictors of local microclimate, with elevation and terrain curvature primarily constraining daily mean temperatures and vapour pressure deficit (VPD), whereas canopy height had a clear dampening effect on microclimate extremes. This buffering effect was particularly pronounced on wind‐exposed slopes but tended to saturate once canopy height exceeded 20 m—suggesting that despite intensive logging, secondary forests remain largely thermally buffered. Nonetheless, at a landscape‐scale microclimate was highly heterogeneous, with maximum daily temperatures ranging between 24.2 and 37.2°C and VPD spanning two orders of magnitude. Based on this, we estimate that by the end of the century forest regeneration could be hampered in degraded secondary forests that characterize much of Borneo's lowlands if temperatures continue to rise following projected trends. Abstract : Written Summary:Local‐scale microclimatic conditions in forest understoreys play a key role in shaping the composition, diversity and function of these ecosystems. Yet our ability to capture microclimate at scales relevant for management and conservation remains inherently limited. By combining a network of microclimate sensors with high‐resolution airborne laser scanning data acquired across a land‐use intensity gradient in Borneo, here we characterise how topography and canopy structure shape variation in microclimate in human‐modified tropical landscapes. We estimate that by 2080 forest regeneration could be hampered in large tracts of degraded secondary forest that make up much of Borneo's lowlands.